Rethinking Management Information Systems / An Interdisciplinary Perspective - Currie Wendy; Galliers Bob (Oxford University Press, 1999)
This book examines influential ideas within management information systems (MIS). List of Figures and Tables, Theoretical and Methodological Perspectives, Researching MIS, Systems Thinking, Structuration Theory, Information Systems and Strategic Management and Performance Evaluation, Strategy-Making in the Information Age, Accounting as a Representational Craft: Lessons for Research on Information Systems, Developing and Implementing Change Programs, Information Systems Development, Deciding the Future for IS Failures: Not the Choice You Might Think, A Historical Analysis of Implementing IS at J. Lyons, Organization and Management Issues, The Cultural Context of Information Management, The Management of Knowledge Workers, Index.